2022
DOI: 10.17706/ijeeee.2022.12.1.30-41
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Internet and Social Media: A Literature Review

Abstract: This article reviews and analyses factors impacting the evolution of the internet, the web, and social media channels, charting historic trends and highlight recent technological developments. The review comprised a deep search using electronic journal databases. Articles were chosen according to specific criteria with a group of 34 papers and books selected for complete reading and deep analysis. The 34 elements were analysed and processed using NVIVO 12 Pro, enabling the creation of dimensions and categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…SMIs have become an object of interest for practitioners and researchers, resulting in numerous scientific publications (e.g., de Castro et al, 2021; Hudders et al, 2021; Vrontis et al, 2020). Research thus far has considered, among other things, the important aspects of building parasocial interactions and the impact of SMIs on consumers' purchasing decisions, providing a solid scientific verification of the business practices used and contributing to the development of this topic in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMIs have become an object of interest for practitioners and researchers, resulting in numerous scientific publications (e.g., de Castro et al, 2021; Hudders et al, 2021; Vrontis et al, 2020). Research thus far has considered, among other things, the important aspects of building parasocial interactions and the impact of SMIs on consumers' purchasing decisions, providing a solid scientific verification of the business practices used and contributing to the development of this topic in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in their literature review, Hudders et al (2021) identified significant research directions related to exploring how influencers can induce behavior change or influence public opinion, thus confirming the need for future research to focus on the appeal of influencers and the effectiveness of their sponsored recommendations. Meanwhile, de Castro et al (2021) pointed out some insights into who SMIs are and how brands and SMIs work together. The authors pointed out a gap in the literature and stressed that research is needed to uncover the impact of SMIs on young people, which may have both desirable and undesirable consequences.…”
Section: Introductionmentioning
confidence: 99%